Modular design of QCA carry flow adders and multiplier with reduced wire crossing and number of logic gates. (12th October 2015) - Zhang, Yongqiang; Lv, Hongjun; Du, Huakun; Huang, Cheng; Liu, Shuai; Xie, Guangjun
Summary: Quantum‐dot cellular automata (QCA) is an emerging technology with the rapid development of low‐power high‐performance digital circuits. In order to reduce the wire crossings and the number of logic gates in QCA circuits, this paper proposes a full adder named Tile full adder based on a 3 × 3 grid module, a Tile bit‐serial adder based on the new full adder and a Diverse Clock Tile bit serial adder (DC Tile bit‐serial) adder based on the new full adder and a DC multiplier network. Based on previously mentioned circuit units an improved carry flow adder (CFA) named Tile CFA and two types of carry delay multiplier (CDM) named Tile CDM and DC Tile CDM (DC Tile CDM) with different sizes are presented. All of the proposed QCA circuits are designed and simulated with QCADesigner. Simulation results show that these circuit designs not only implement the logic functions correctly but also achieve a significant performance improvement. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : To resolve the problems caused by the limitations of complementary metal–oxide–semiconductor‐based technology, a new CFA, two CDM circuits in QCA‐based field are proposed. Simulation results and comparison results show that these circuits achieve better performances.